2020
DOI: 10.1007/s40121-020-00282-w
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the Safety and Tolerance Profile of Micafungin with that of Other Echinocandins and Azoles in Patients with Pre-existing Child–Pugh B or C Liver Disease: A Case–Control Retrospective Study

Abstract: Introduction: To assess the association between exposure to micafungin, other echinocandins, or azoles and the development of short-term liver injury (STLI) or long-term liver injury (LTLI) in patients with Child-Pugh B or C liver disease. Methods: Multicenter case-control study of patients with Child-Pugh B or C liver disease who received antifungals (AF) for C 72 h (May 2009-May 2015) in six Spanish and Italian hospitals. All micafungin patients were randomly matched with one patient who received another ech… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 42 publications
(65 reference statements)
0
2
0
Order By: Relevance
“…In analyses stratified on comparing to echinocandins, no signal of increased hepatic dysfunction event reporting was found (ROR<1). In previous studies, the echinocandins were considered to have a lower hepatotoxicity when compared with triazoles [14]. A network meta-analysis and systematic review on adverse reactions of antifungal drugs also showed that caspofungin was more significantly associated with a lower incidence of hepatobiliary disorders [15].…”
Section: Signal Values Associated With Hepatic Dysfunction At Pt Levelmentioning
confidence: 99%
“…In analyses stratified on comparing to echinocandins, no signal of increased hepatic dysfunction event reporting was found (ROR<1). In previous studies, the echinocandins were considered to have a lower hepatotoxicity when compared with triazoles [14]. A network meta-analysis and systematic review on adverse reactions of antifungal drugs also showed that caspofungin was more significantly associated with a lower incidence of hepatobiliary disorders [15].…”
Section: Signal Values Associated With Hepatic Dysfunction At Pt Levelmentioning
confidence: 99%
“…71,72 Although, caspofungin and micafungin undergo substantial hepatic metabolism, apparently, in two smaller clinical experiences only minimal changes in pharmacokinetics of caspofungin has been reported in patients with liver failure, apparently with no clinical impact, even in patients with Child-Pugh B or C liver disease. 75,76 On the other hand, an increase of the AUC in patients with chronic liver insufficiency during caspofungin treatment, resulted in a manufactory dose reduction recommendation for patients with CHILD Pugh B or C liver disease. 77 Nevertheless, Gustot et al 78 recently showed that dose reduction of caspofungin to 35 mg in cirrhotic patients resulted in lower drug exposure than that obtained by non-cirrhotic patients using the conventional approved dose.…”
Section: Ther Apy Of Ifi In Liver Impairmentmentioning
confidence: 99%